Perancangan Chatbot Pusat Layanan Kantor LAZISMU DIY dengan Pendekatan Natural Language Processing dan Algoritma Brute Force - Dewi Soyusiawaty; Almira Haswinitha (Teknik Informatika Universitas Pamulang, 2023)
The service center in a company or agency is a place to serve various kinds of questions and customer complaints served by a customer service. However, it is undeniable that the role of customer service has many shortcomings, such as having to answer repeated questions given to different customers and limited hours. With the rapid development of technology, this role is now supported by an interactive automation system in answering questions given to customers. The automation system in question is a virtual assistant in the form of a chatbot. The application in the chatbot design is built by utilizing text mining reasoning, applying patterns between user input and the database using the Brute Force algorithm, and the process of correcting erroneous words using the Peter Norvig algorithm. Text mining can be defined as the process of extracting the required information from textual sources, the Brute Force algorithm performs a pattern from left to right, and the Peter Norvig method for correcting words by deciphering each letter in the wrong word. The chatbot design is useful in increasing the quality and effectiveness of services at LAZISMU DIY. The chatbot system that was built certainly passed the method validation test process. Testing is done by implementing the black-box testing method. The test results obtained are based on 7 test scenarios with a total of 96 questions, which is 93%.